2020
DOI: 10.3847/1538-4357/ab5fdd
|View full text |Cite
|
Sign up to set email alerts
|

The Strength of the 2175 Å Feature in the Attenuation Curves of Galaxies at 0.1 <  z ≲ 3

Abstract: We update the spectral modeling code MAGPHYS to include a 2175Å absorption feature in its UV-tonear-IR dust attenuation prescription. This allows us to determine the strength of this feature and the shape of the dust attenuation curve in ∼5000 star-forming galaxies at 0.1 < z 3 in the COSMOS field. We find that a 2175Å absorption feature of ∼1/3 the strength of that in the Milky Way is required for models to minimize residuals. We characterize the total effective dust attenuation curves as a function of severa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 90 publications
6
52
1
Order By: Relevance
“…The normalization 13 , R (V)=4.93 ± 0.37, is much larger than most extinction curves (typically with R(V)=3.1 or smaller, with few exceptions), and larger than the value found for many attenuation curves, including the SB one (R (V)=4.05±0.80 Calzetti et al 2000). However, this is consistent with the R (V) values found by Battisti et al (2020) for z>1 galaxies. When normalized to k(λ)/k(V)=1, the FUV slope in equation 8 is close to that of the MW extinction curve, and in-between those of the SB attenuation and SMC extinction curves (Figure 15, right).…”
Section: The 'Net' Attenuation Curve In the Center Of Ngc 3351supporting
confidence: 82%
“…The normalization 13 , R (V)=4.93 ± 0.37, is much larger than most extinction curves (typically with R(V)=3.1 or smaller, with few exceptions), and larger than the value found for many attenuation curves, including the SB one (R (V)=4.05±0.80 Calzetti et al 2000). However, this is consistent with the R (V) values found by Battisti et al (2020) for z>1 galaxies. When normalized to k(λ)/k(V)=1, the FUV slope in equation 8 is close to that of the MW extinction curve, and in-between those of the SB attenuation and SMC extinction curves (Figure 15, right).…”
Section: The 'Net' Attenuation Curve In the Center Of Ngc 3351supporting
confidence: 82%
“…Observations have shown that the IRX-β relation varies with stellar mass (Bouwens et al 2016(Bouwens et al , 2020Reddy et al 2018;Fudamoto et al 2020), infrared (IR) luminosity (Buat et al 2012;Casey et al 2014), age (Siana et al 2009;Reddy et al 2010;Shivaei et al 2015), redshift (Capak et al 2015;Pannella et al 2015), and intrinsic β 0 (β for a dust-free system; Boquien et al 2012;Reddy et al 2018;Schulz et al 2020). These variations are linked to the diversity of galaxies' attenuation curves, seen in previous studies (e.g., Kriek & Conroy 2013;Scoville et al 2015;Battisti et al 2020). The attenuation curve variations stem from two main sources: (a) different geometrical distributions of dust with respect to stars (and different dust optical depths), and (b) different dust grain properties, which affect the shape of the underlying extinction curve irrespective of the dust-star geometry (see the review by Salim & Narayanan 2020).…”
Section: Introductionmentioning
confidence: 55%
“…UV luminosity and β-To derive the UV continuum slope, β, and UV luminosity density (L ν ) at 1600 Å, we fit a power law to the photometry at rest-frame λ=1260-2600 Å, f λ ∝λ β (COSMOS and UDS have good rest-UV coverage with at least four photometric points in this range). We avoid the wavelength range of λ=1950-2400 Å, as it may potentially be affected by the 2175 Å UV bump, seen in the attenuation curve of highmetallicity galaxies at these redshifts (Scoville et al 2015;Battisti et al 2020;Shivaei et al 2020). Hereafter, νL ν at 1600 Å is referred to as UV luminosity, L(UV).…”
Section: Sample and Datamentioning
confidence: 99%
“…) that can be used to handle the attenuation of old and young populations and thus change the effective attenuation law (e.g., Battisti et al 2020). The difference in dust geometry is therefore handled through this parameter.…”
Section: The Cigale Codementioning
confidence: 99%